Risk identification in petroleum upstream projects - Phan Ngoc, Trung; Nguyen Thi Thanh, Le; Hoang Thi, Phuong; Nguyen Thi Thuy, Dung; Pham Kieu, Quang; Nguyen Thi Thu, Phuong; Phung Le, Mai; Tran Thi Minh, Anh; Nguyen Ngoc, Tu (Petrovietnam Journal, 2019)
Being an inevitable attribute of investment activities, risk can have either positive or negative impacts. Risk identification is not only an important step in the process of project assessment and decision making, but also needs to be regularly updated for investment management, operational management and change management throughout the lifecycle of the projects. The paper presents the importance of risk identification and how it is implemented for petroleum upstream projects. Based on the actual operations of Petrovietnam and many international oil and gas companies, the authors identify risks to be faced by petroleum upstream projects (geological conditions, reserves, production output, trade, market, economics, finance, investment environment, policies and mechanism, etc.), which will be the basis for making implementation plans and selecting optimal solutions to achieve the project objectives.